Etiology and outcome of Neonatal Acute Kidney Injury in a Special Care Baby Unit (Northern International Medical College Journal, 2016)
Background : The cause of acute kidney injury (AKI) in neonate is multifactorial. The short-term outcome of AKI in newborns is highly dependent on the underlying etiology, the condition of other organs, and the facilities for renal replacement therapy.Objective : The aims of the present study were to find out the etiology and immediate outcome of AKI in neonate.Methodology : This observational study was done over a period of six months, at special care baby unit (SCABU) in Dhaka Medical College Hospital (DMCH). Neonates (aged 3-28 days) admitted in SCABU, who had AKI were the study population. Among them 44 neonates with AKI were included purposivly. AKI was diagnosed and classified by pediatric RIFLE (pRIFLE) staging criteria. Etiology of AKI was find out by dividing pre renal, renal and post renal cause of AKI. All neonates were treated conservatively and with intermittent peritoneal dialysis (IPD) as needed. Immediate hospital outcome was determined by improved with normal renal functions; improved with impaired renal functions and death.Result : The diagnosis based on estimated creatinine clearance (eCCL) criteria of pRIFLE showed that 43.2% neonates were at risk (R) stage, 22.7% were at injury (I) stage and 34.1% of neonates were at Failure (F) stage of AKI. Among 44 neonates 21 were male and 23 were female. Pre renal cause of AKI is predominant in this series. More than two-thirds (68.2%) of the neonates experienced perinatal asphyxia stage-II and III and 52.3% were exposed to meconium stained liquor during delivery. Septicemia with shock, history of aminoglycoside use were reported to be 59.1%, 52.3% respectively. Post renal cause was found in 16% neonates, like obstructive uropathy due to posterior urethral valve, exstrophy bladder and cloacal exstrophy. Neonate at Failure stage of AKI (n=15) had a significantly longer stay at SCABU (p < 0.001). Multiorgan failure was found to be significantly higher in failure group (p = 0.026). Majority of the failure group needed dialysis (p < 0.001). Most of the neonate at risk and injury stage was improved with normal renal functions. The resolution from AKI was almost similar among the groups (p = 0.885). The mortality was progressively higher from Risk to Failure Groups (p = 0.106). Overall 27% of the neonates diagnosed as AKI died from this illness, 57% improved with normal renal function and 16% improved with impaired renal function.Conclusion : The study concluded that perinatal asphyxia, septicemia with shock and use of aminoglycosides were the commonest cause of AKI in neonate. The mortality was higher in Failure group.Northern International Medical College Journal Vol.7(2) Jan 2016: 127-130